2017
DOI: 10.1111/eea.12583
|View full text |Cite
|
Sign up to set email alerts
|

Aphid orientation and performance in glasshouses under different UV‐A/UV‐B radiation regimes

Abstract: Visual cues leading to host selection and landing are of major importance for aphids and evidence suggests that flight activity is very dependent on ultraviolet (UV)-A radiation in the environment. At the same time research on insect plant hosts suggest that the UV-B component can deter some pests via changes in secondary metabolite chemistry. Here, we examine the potential of UV (UV-A/UV-B) radiation to control insect pests in the glasshouse environment. We first examined artificial exposure to UV-B and the p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 48 publications
0
6
0
Order By: Relevance
“…Thus, it is thought that the response of WFT flying towards the ceiling was mainly caused by the presence of UV-A light and not by the white light illuminating the wind tunnel. UV-light is known to be an important cue in aiding invertebrates in navigation, orientation [ 88 ], and the dispersion of pest insects [ 89 , 90 , 91 ] including thrips [ 92 ]. It also elicits phototaxis in insects [ 93 , 94 ] and is thought to be related to wavelength-specific behaviours [ 88 , 93 , 94 ] such as migration or escape response [ 94 ].…”
Section: Discussionmentioning
confidence: 99%
“…Thus, it is thought that the response of WFT flying towards the ceiling was mainly caused by the presence of UV-A light and not by the white light illuminating the wind tunnel. UV-light is known to be an important cue in aiding invertebrates in navigation, orientation [ 88 ], and the dispersion of pest insects [ 89 , 90 , 91 ] including thrips [ 92 ]. It also elicits phototaxis in insects [ 93 , 94 ] and is thought to be related to wavelength-specific behaviours [ 88 , 93 , 94 ] such as migration or escape response [ 94 ].…”
Section: Discussionmentioning
confidence: 99%
“…On 42-day-old eggplants (induced effect), any exposure time or supplementary UV combination significantly reduced the number of whiteflies settled. Indirect effects of plants previously exposed to UV radiation on insect avoidance behavior have previously been reported for aphids (Dáder et al 2017;Vänninen et al 2010).…”
Section: Discussionmentioning
confidence: 83%
“…A 30-min daily dose of UV radiation did not alter the concentration of carbon or nitrogen, nor any of the detectable amino acids or sugars except for galactose. In addition Dáder et al (2014Dáder et al ( , 2017 found out on similar assays conducted on eggplants and peppers, that the content of phenolics and carotenoids increased. Leaves of eggplants harvested for biochemical analysis had been also subjected to the different UV treatments and used for the whitefly orientation assays; therefore, the combination of both might have influence the chemical parameters measured here.…”
Section: Discussionmentioning
confidence: 88%
“…Competitors of insects were reportedly less affected than their targets by altered UV exposure, and UV-exposed plant tissues may be capable of releasing increased levels of volatile compounds that are more efficient in attracting parasitoids ( Foggo et al, 2007 ; Legarrea et al, 2014 ; Dáder et al, 2015 ). Depending on specific target plant–phyllosphere interactions, strategies for plant growth may include moderate exposure of plants to UV-B at early growth stages to induce defense mechanisms and not affect plant growth and yield, and later suppression of UV light to restrict insect entrance and herbivore attack ( Elfadly et al, 2016 ; Dáder et al, 2017 ). Each situation should be evaluated on a case-by-case basis, considering as well plant specific tolerance to UV irradiance and the tight control of UV conditions, including the spectrum provided by selected shading or light bulbs, and the intensity.…”
Section: The Role Of Lightmentioning
confidence: 99%